Intraventricular Catheter-Associated Rothia mucilaginosa Bacteremia in a Neutropenic Patient. Issue 2 (March 2021) - Li, Monica; Lin, Doris
Abstract : Abstract: Rothia mucilaginosa is a pleomorphic gram-positive coccobacilli found commensally in the nose and throat. Over the past several decades, it has been recognized as a rare cause of severely invasive disease in the immunocompromised. We present an uncommon case of neutropenic fever caused by R. mucilaginosa bacteremia with a recently placed Ommaya reservoir intraventricular catheter system as a potential nidus. The patient recovered after antibiotic and tbo-filgrastim therapy, as well as removal of the catheter.